Placental growth factor level is correlated with intrapartum fetal heart rate findings - Hiroaki Tanaka; Kayo Tanaka; Sho Takakura; Naosuke Enomoto; Shintaro Maki; Tomoaki Ikeda (BMC, 2022)
Abstract Objective Here, we tested the correlation between maternal placental growth factor (PlGF) and fetal heart rate (FHR) monitoring findings. Methods We included 35 women with single pregnancies from 35 to 42 weeks of gestation who were hospitalized owing to onset of labor. Blood samples were collected at the start of labor. Intrapartum FHR monitoring parameters included total deceleration area, average deceleration area (mean deceleration area per 10 min), and five-tier classification level. Results Of the 35 women, 26 (74%) had vaginal delivery and 9 (26%) had cesarean section. After excluding 2 women who had cesarean section for arrest of labor, we analyzed 26 women who had vaginal delivery (VD group) and 7 who had cesarean section for fetal indications (CSF group). PlGF level was significantly higher in the VD group (157 ± 106 pg/ml) than in the CSF group (74 ± 62 pg/ml) (P = 0.03). There were no significant correlations between PlGF and total (r = -0.07) or average (r = -0.08) deceleration area.　There was a significant negative correlation (r = -0.42, P = 0.01) between PlGF and the percentage of level 3 or higher in the five-level classification. Conclusion PlGF was correlated with FHR monitoring findings and might be a promising biomarker of intrapartum fetal function.